The influence of a different accounting system on informative value of selected financial ratios - Malíková, Olga; Brabec, Zdeněk (Technological and Economic Development of Economy, 2012)
In recent global world the importance of financial markets is growing as well as the amount of capital distributed through these markets. To enable optimal efficiency of these markets the best investment opportunities has to be chosen. An alternative how to compare and select suitable companies to invest in is represented by a financial analysis of financial statements. The results of financial ratios are mainly influenced by the presumptions according to those the financial statements have been prepared. Therefore, in this article there is analysed if and eventually how significant the input data, influence the results of financial ratios. Firstly, the description of financial ratios that are used in following analysis is made. After that, there are analysed the requirements of Czech legislation and IAS/IFRS and their influence on financial statements. Then, the influence of five selected accounting transaction on balance sheets and income statements that are prepared once according to the Czech legislation and for the second time according to the IAS/IFRS is analysed. The final part tries to examine if and how strong the impact of different accounting system on the results of the selected financial ratios is.